(2019) - Robert Ulewicz (Sciendo, 2019)
The magazine's publications deal with issues related to work safety. Both in the area of occupational health and safety, organization of the workplace (technical aspects) and the environment (environmental factors in working conditions). The publications presented combine legal requirements in the field of work safety with the technical solutions that are designed to meet the minimum requirements. They present and analyze the requirements of technological processes carried out at workplaces. Sociological issues are also carried out in the analyzes, in the scope of training and creating a safety culture within production enterprises. Scope Subject areas, suitable for publication, include the following fields: Health and safety management systems Technological safety The role of the human factor in occupational health and safety management systems Safety of technical facilities operation (safety engineering) Environmental safety management Safety management of products and services Management of occupational risk Economical aspects of occupational health and safety Legal aspects of health and safety at work Safety in material engineering Safety in civil engineering Product quality and user safety Safety logistics Safety in innovation and their transfer Knowledge and information management 7th International Conference SYSTEM SAFETY HUMAN - TECHNICAL FACILITY – ENVIRONMENT e-Book ISBN: 978-3-11-060540-2 8th International Conference SYSTEM SAFETY HUMAN - TECHNICAL FACILITY – ENVIRONMENT e-Book ISBN: 978-83-957204-3-7 Archiving Sciendo archives the contents of this journal in　Portico　- digital long-term preservation service of scholarly books, journals and collections. Plagiarism Policy The editorial board is participating in a growing community of　Similarity Check System's　users in order to ensure that the content published is original and trustworthy. Similarity Check is a medium that allows for comprehensive manuscripts screening, aimed to eliminate plagiarism and provide a high standard and quality peer-review process.